(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
In the famed speech delivered during the negotiations in Naupaktos, Agelaos among other things advises Philip V to turn his attention towards the West and the struggle between Rome and Carthage. The similarities with the advice that Demetrios of Pharos previously gave the king is a reason to doubt its authenticity. That the advice is ascribed to an Aitolian should not be taken as an argument in favour of its authenticity, but quite the contrary fits in with Polybios’ generally negative image of the Aitolians in this period. Although its authenticity can not be proved with certainty, at least in historical context that may not be too important, for the future actions of Philip V show that it had little impact on the decision for concluding the Peace of Naupaktos.